2012
DOI: 10.1111/boc.201100116
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional activity of co‐activator AIB1 is regulated by the SUMO E3 Ligase PIAS1

Abstract: Taken together, these results suggested that PIAS1 may play a crucial role in the regulation of AIB1 transcriptional activity through sumoylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…We have previously shown that the AIB1 is required for breast cancer cell proliferation and demonstrated that its transcriptional activity is up-regulated by phosphorylation and down-regulated by sumoylation, and identified PIAS1 as the SUMO E3 ligase that can enhance the sumoylation of AIB1, thereby down-regulating AIB1 transcriptional activity [24], [25]. In this study, we used a combined molecular and cellular approach to characterize the role of AIB1 in EMT.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the AIB1 is required for breast cancer cell proliferation and demonstrated that its transcriptional activity is up-regulated by phosphorylation and down-regulated by sumoylation, and identified PIAS1 as the SUMO E3 ligase that can enhance the sumoylation of AIB1, thereby down-regulating AIB1 transcriptional activity [24], [25]. In this study, we used a combined molecular and cellular approach to characterize the role of AIB1 in EMT.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to SnoN, PIAS1 triggers sumoylation of other proteins including c-myc [42], Mdm2 [31] and AIB1 [43]. Thus, it would be interesting to evaluate the contribution of other PIAS1 SUMO substrates in its potential ability to regulate breast cancer invasiveness and metastasis, and to its utility as a biomarker in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Human breast cancer cell lines MCF-7, T47D, MCF10A and MDA-MB-231 have been used in our previous studies [31]–[34]. MCF-7 and MDA-MB-231 cells were cultured in Dulbecco's Modified Eagle's Medium (DMEM) containing 10% fetal bovine serum (Hyclone, Logan, UT), 100 µg/ml penicillin and 100 µg/ml streptomycin.…”
Section: Methodsmentioning
confidence: 99%